Ebook Embroidery Variations to Improve Students’ Learning Outcomes in Basic Embroidery Technique Courses - Rambe, Armaini; Juliarti; Rahma Dewi, Eka; Anggraini, Yudhistira (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
Many students experience the difficulty of applying the right variations of embroidery to clothing. The available learning resources only contain material on clothing variations without providing appropriate examples for applying embroidery variations to clothing. Hence, this research aims to develop an electronic book on the application of embroidery variations to clothing. The research is Research and Development (R&D) research. The development model used is the Brog and gall model. Validation of teaching materials is carried out by material experts and media experts. The validation results from material experts indicates 92.06% in the very feasible category. The validation results from media experts reveals an average of 94.43%, which was very feasible. Small group trials indicates an average result of 82.87% in the very feasible category. Large group trials reveals an average score of 87.85% in the very feasible category. Thus, it can be concluded that the e-book on embroidery variations is very suitable for use in basic embroidery technique courses. The development of an electronic book on embroidery variations can facilitate the delivery of practical material in applying embroidery variations on clothing so as to increase students' understanding of learning basic embroidery techniques.